2008
DOI: 10.2119/2007-00113.masuda
|View full text |Cite
|
Sign up to set email alerts
|

Soluble FcγRIIIaMϕ Levels in Plasma Correlate with Carotid Maximum Intima-Media Thickness (IMT) in Subjects Undergoing an Annual Medical Checkup

Abstract: Macrophages play a major role in the development of vascular lesions in atherogenesis. The cells express FcγRIIIa (CD16) identical to that in NK cells, but with a cell type-specific glycosylation, and these soluble forms (sFcγRIIIa) are present in plasma. We measured sFcγRIIIa Mφ derived from macrophages in plasma from subjects undergoing an annual medical checkup. The levels of sFcγRIIIa Mφ increased with age, and correlated positively with body mass index, blood pressure, LDL cholesterol to HDL cholesterol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…57 Moreover, sFc gRIIIa MF concentration in the plasma was correlated with carotid maximum intima-media thickness and a number of risk factors for atherosclerosis, such as aging, current smoking, diabetes, hypertension, LDL-cholesterol/HDL-cholesterol ratio and family history of atherosclerotic diseases. 58 These findings indicate that the macrophages are activated during the process of atherosclerosis, and sFcg RIIIa MF serves as a novel biomarker for atherosclerosis. Pfeiffer et al 59 performed quantitative flow cytometry to measure the expression of Fc gRI and Fc gRIIA on peripheral monocytes in patients with severe atherosclerosis, and found that the expression of Fc g RIIA on peripheral monocytes was significantly decreased in patients with clinical atherosclerosis compared with control subjects and it was positively correlated with serum HDL-cholesterol concentrations.…”
Section: Fc Gr Polymorphisms and Expression In The Vascular Atherosclerotic Disease: Insight From Clinical Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…57 Moreover, sFc gRIIIa MF concentration in the plasma was correlated with carotid maximum intima-media thickness and a number of risk factors for atherosclerosis, such as aging, current smoking, diabetes, hypertension, LDL-cholesterol/HDL-cholesterol ratio and family history of atherosclerotic diseases. 58 These findings indicate that the macrophages are activated during the process of atherosclerosis, and sFcg RIIIa MF serves as a novel biomarker for atherosclerosis. Pfeiffer et al 59 performed quantitative flow cytometry to measure the expression of Fc gRI and Fc gRIIA on peripheral monocytes in patients with severe atherosclerosis, and found that the expression of Fc g RIIA on peripheral monocytes was significantly decreased in patients with clinical atherosclerosis compared with control subjects and it was positively correlated with serum HDL-cholesterol concentrations.…”
Section: Fc Gr Polymorphisms and Expression In The Vascular Atherosclerotic Disease: Insight From Clinical Studiesmentioning
confidence: 90%
“…57 Moreover, sFc γ RIIIa MΦ concentration in the plasma was correlated with carotid maximum intima-media thickness and a number of risk factors for atherosclerosis, such as aging, current smoking, diabetes, hypertension, LDL-cholesterol/HDL-cholesterol ratio and family history of atherosclerotic diseases. 58 These findings indicate that the macrophages are activated during the process of atherosclerosis, and sFc γ RIIIa MΦ serves as a novel biomarker for atherosclerosis. Pfeiffer et al .…”
Section: Fc γ R Polymorphisms and Expression In The Vascular Atherosclerotic Disease: Insight From Clinical Studiesmentioning
confidence: 99%
“…However, linear regression analysis showed non-significant results for continuous maximum cIMT values. Others have reported that soluble FcγRIIIA is associated with maximum cIMT [ 27 ], that the FcγRIIIA VV-genotype is inversely related to the extent of coronary artery disease [ 6 ] and that the FcγRIIA R allele is associated with impaired endothelial vasodilation in patients with hypercholesterolemia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%